LIVED EXPERIENCE OF NURSES IN CARING FOR PERSONS WITH OUT-OF-HOSPITAL CARDIAC ARREST IN RURAL AREAS OF EAST JAVA INDONESIA: A PHENOMENOLOGICAL STUDY - Janes Jainurakhma; Mochamad Soleh; Ni Luh Dewi Ayu Sita; Ika Yuli Astuti (Belitung Nursing Journal, 2020)
Background: Out-of-hospital cardiac arrest can occur anywhere, including in rural areas. Nurses are demanded to have skills for critical care to save lives. Objective: This study aimed to explore lived experience of nurses in caring for persons with out-of-hospital cardiac arrest in the rural areas of East Java, Indonesia. Methods: This study employed a phenomenological research design. Five nurses were selected from five village health posts using a purposive sampling. A semi-structure interview was used to collect data. Colaizzi’s method was used for data analysis. Results: Four themes emerged, including (1) being fast and responsive, (2) needing a family trust, (3) feeling worried, and (4) lacking personnel and infrastructure. Conclusion: The role of nurses in saving lives of persons with out-of-hospital cardiac arrest is very important. It is suggested for the nurses to always improve the quality of knowledge management of persons with critical conditions, provide understanding of basic life support in community, increase the trust of family in nurses, and improve the collaboration between nurses and community. The government also need to provide better emergency equipment and add health personnel in community.